Functional disabilities and its associated factors among elderly residents in private nursing homes in Kuantan - Md Aris, Mohd Aznan; Mazlan, Mazilah; Mohd Rus, Razman; Samsudin, Suhaiza (2021)
Malaysia is on its way to becoming an aging society, which number will cross 15% of the population by the year 20301 . Residing in a nursing home poses a greater challenge for the elderly physically and mentally. The inability to complete basic activities of daily living may lead to poorer quality of life. This study aims to determine the prevalence of functional disabilities and its associated factors among elderly in private nursing homes in Kuantan.